Theoretical framework of a trip generation model in an urban area - Kadar Hamsa, Abdul Azeez (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2005)
Transportation is one of the important elements of urban infrastructure to ensure efficient operational and functioning of an urban area. Smooth and orderly traffic movement will, eventually, ensure efficiency of the road network with minimum delay. Trip generation process is the first step of the four-step travel demand forecasting models. A trip, for any purposes, will begin from a zone of origin and end at a zone of destination. It is important to determine the number of trips originated and destined from and to various zones in a selected area. Thus, the generation of trip-ends at origins and destinations is determined by using trip generation model. The methodology of the models used to analyse the trip generation rate is discussed in this paper. The limitations to apply these models on the collected date is also reviewed and discussed.